Using computers to enable self‐management of aphasia therapy exercises for word finding: the patient and carer perspective. Issue 5 (18th June 2013) - Palmer, Rebecca; Enderby, Pam; Paterson, Gail
Abstract: Background: Speech and language therapy (SLT) for aphasia can be difficult to access in the later stages of stroke recovery, despite evidence of continued improvement with sufficient therapeutic intensity. Computerized aphasia therapy has been reported to be useful for independent language practice, providing new opportunities for continued rehabilitation. The success of this option depends on its acceptability to patients and carers. Aims: To investigate factors that affect the acceptability of independent home computerized aphasia therapy practice. Methods & Procedures: An acceptability study of computerized therapy was carried out alongside a pilot randomized controlled trial of computer aphasia therapy versus usual care for people more than 6 months post‐stroke. Following language assessment and computer exercise prescription by a speech and language therapist, participants practised three times a week for 5 months at home with monthly volunteer support. Semi‐structured interviews were conducted with 14 participants who received the intervention and ten carers ( n = 24). Questions from a topic guide were presented and answered using picture, gesture and written support. Interviews were audio recorded, transcribed verbatim and analysed thematically. Three research SLTs identified and cross‐checked themes and subthemes emerging from the data. Outcomes & Results: The key themes that emerged were benefits and disadvantages of computerized aphasia therapy, need for help and support, and comparisons with face‐to‐face therapy. The independence, flexibility and repetition afforded by the computer was viewed as beneficial and the personalized exercises motivated participants to practise. Participants and carers perceived improvements in word‐finding and confidence‐talking. Computer practice could cause fatigue and interference with other commitments. Support from carers or volunteers for motivation and technical assistance was seen as important. Although some participants preferred face‐to‐face therapy, using a computer for independent language practice was perceived to be an acceptable alternative. Conclusions & Implications: Independent computerized aphasia therapy is acceptable to stroke survivors. Acceptability can be maximized by tailoring exercises to personal interests of the individual, ensuring access to support and giving consideration to fatigue and life style when recommending practice schedules.